A segurança interna dos Estados Unidos da América e os atentados terroristas de 11 de setembro de 2001: um estudo sobre as mudanças na segurança aeroportuária estadunidense após o 9/11 - Miwa, Luiz Carlos Fumiaki (2013)
The objetive of this thesis can be expressed as the analysis of the relationship between the phenomenon of terrorism and internal security of the United States, through the study of changes in the political, and the measures implemented by this political power to combat threats arising terrorist groups, after the attacks of September 11, 2001, particularly in the aviation and airport environments. The methodology was based on the literature and on documents collected on the internet. The factors defended by Buzan, Waever and Wilde (1998) political, economic, military, environmental and social were analyzed as we believed that they were linked to the process of securitization between contemporary states. We used also as a specific variable, airport security, through the study of aerial movement, both cargo and passengers, as well as luggage lost. It was thought, in this way, that would be created a representation of the influence of the terrorist attacks in the weakening or not the USA. The option for the study of air transportation can be justified in terms of the number of movements, both passenger and cargo, performed around the world, especially to and from the United States daily. The difficulty of inspection and control of what is transported, is a factor able to put in evidence the risk to the safety of the country, besides constituting a vulnerability by inserting illicit artifacts, including explosives, chemical or biological agents. So, in short, the focus of debate, conducted throughout this work, revolves around the issue of terrorism and the need for securitization by the American political power, depending on the acts committed by extremists